2018
DOI: 10.1002/mp.13241
|View full text |Cite|
|
Sign up to set email alerts
|

A machine learning texture model for classifying lung cancer subtypes using preliminary bronchoscopic findings

Abstract: Purpose Bronchoscopy is useful in lung cancer detection, but cannot be used to differentiate cancer types. A computer‐aided diagnosis (CAD) system was proposed to distinguish malignant cancer types to achieve objective diagnoses. Methods Bronchoscopic images of 12 adenocarcinoma and 10 squamous cell carcinoma patients were collected. The images were transformed from a red–blue–green (RGB) to a hue–saturation–value (HSV) color space to obtain more meaningful color textures. By combining significant textural fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Numerous studies [19][20][21][22] have demonstrated the application of CADx tools for diagnosing lung [19][20][21] and breast [19,22] lesions. Cheng et al [19] investigated the deep learning capability for the diagnosis of breast lesions in ultrasound (US) images and pulmonary nodules in CT scans.…”
Section: Computer-aided Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies [19][20][21][22] have demonstrated the application of CADx tools for diagnosing lung [19][20][21] and breast [19,22] lesions. Cheng et al [19] investigated the deep learning capability for the diagnosis of breast lesions in ultrasound (US) images and pulmonary nodules in CT scans.…”
Section: Computer-aided Diagnosismentioning
confidence: 99%
“…Figure 4 illustrates several cases of breast lesions and pulmonary nodules in US and CT images, respectively, differentiated with deep learning-based CADx [19]. Feng et al [20] and Beig et al [21] studied the classification of lung lesions on endo-bronchoscopic images [20] with logistic regressions, and non-small cell lung cancer (NSCLC) adenocarcinomas distinctions from granulomas on non-contrast CT [21] using support vector machine (SVM) and neural network (NN). The reported results indicated an accuracy of 86% in distinguishing lung cancer types, e.g., adenocarcinoma and squamous cell carcinoma [20].…”
Section: Computer-aided Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Using ML in bronchoscopy, to analyse images and diagnose potential cancers, has been explored. One study achieved 86% diagnostic accuracy . However, treatment decisions are better informed by the definitive histology results, which are typically reported within days.…”
mentioning
confidence: 99%
“…One study achieved 86% diagnostic accuracy. 5 However, treatment decisions are better informed by the definitive histology results, which are typically reported within days. Real-time highlighting of potentially missed lesions could be a more useful approach, and analogous efforts have shown promise in colonoscopy.…”
mentioning
confidence: 99%